Pertimbangan Hakim dalam Penilaian Alat Bukti Surat pada Perkara Penetapan Ahli Waris - Ni Made Sinthya Kusuma Arisanthi; I Nyoman Putu Budiartha; I Nyoman Gede Sugiartha (Warmadewa Press, 2021)
In Heritance is everything in the form of treasure relics left by the heir to the beneficiary, which is that this inheritance can be moving objects and the objects do not move or be rights and obligations. Lately very many disputes arising in consequence in the dividing of the inheritance, which, between the rights and obligations of the unbalanced or in the dividing of the inheritance that is not in accordance with the wishes of the heirs. The dividing of inheritance should be using wills avoiding disputes among the heirs, the absence of a will the heir must prove with evidence of tools that have been specified in the law. One tool evidence supports a very authentic and has the power of proof most perfect IE tool written evidence or mail. From the background of the above, the authors take the title Considerations in the Assessment of the Evidence the Judge a Letter in the Case of Determination of Heirs. In this study, used normative research, so that it can be formulated as follows: the issue of whether the evidence of a letter submitted by the applicant was the beneficiary designation in accordance with the law of civil liability, as well as how the Tribunal judges considering the evidence a letter to grant the petition for dermination of the heirs, from the formulation of the problem can be explored regarding the evidence of tools able to convince at the same time as the consideration of judges in disconnected things of the expert determination the heir. The goals of this research are: to know the strength of the evidence of a letter in the system of succession in Indonesia, as well as to know the legal reasoning used by the judge as the consideration.